Implementasi Proyek Penguatan Profil Pelajar Pancasila - Profil Pelajar Rahmatan Lil Alamin (P5-PPRA) dalam Membangun Moderasi Beragama dan Pendidikan Karakter - Susanti, Linna; Sugiyo, Sugiyo; Mulyo, A. Mufrod Teguh (Fahima, 2025)
This study aims to analyze 1) Implementation of the Pancasila Student Profile Strengthening Project - Rahmatan Lil Alamin Student Profile (P5-PPRA) in building religious moderation and character education. 2) Dimensions of religious moderation and character education values achieved in the implementation of the project to strengthen the profile of Pancasila students - rahmatan lil alamin student profile (P5-PPRA). 3) The dynamics of the implementation of the project to strengthen the profile of Pancasila students - the profile of students rahmatan lil alamin (P5-PPRA) in building religious moderation and character education. This research is a type of qualitative research, which obtains research results through interview techniques, observation, and also data collection that is considered to complement the author's research data. This research is located at MTs N 4 Mojokerto in the 2023/2024 academic year. This study concluded that 1) The implementation of the P5-PPRA in building religious moderation and character education at MTs N 4 Mojokerto has been running according to the criteria and stages, which are analyzed through the five stages of implementing P5-PPRA in madrasas in the P5-PPRA implementation guidebook. 2) The dimensions of the value of the Pancasila student profile strengthening project - Rahmatan lil alamin student profile (P5-PPRA) achieved in building religious moderation are Civilized (ta'addub), Exemplary (qudwah), Balanced (tawazun), Deliberation (syura), Citizenship and nationality (muwatanah), Tolerance (tasamuh), Equality (musawah). 3) Several dynamics of the implementation of the Pancasila Student Profile Strengthening Project - Rahmatan Lil Alamin Student Profile (P5-PPRA) in building Religious Moderation and Character Education at MTs N 4 Mojokerto in the 2023/2024 Academic Year, including supporting and inhibiting factors in the implementation of project activities that come from internal or external parties to the madrasah.